Differentiation and Eating Disorder Symptoms Among Males. (January 2014) - Buser, Juleen K.; Gibson, Sandy
We explored the relationship between four domains of differentiation of self and eating disorder symptoms among male college students. While all differentiation domains were significantly correlated with eating disorder symptoms, only two domains were statistically significant in a regression. Drawing from these results, we discuss family counseling implications.